Religion and Social Construction: The Study of Suwuk and Azimat in the Perspective of Modern Society - Ishmah, Nihayatul; A'yun, Qurrotul (http://jagadalimussirry.com/, 2021)
Public belief regarding suwuk treatment and the use of azimat is ingrained even before it is scientifically proven . Several practices of suwuk and the use of azimat in society show a connection with the belief in Islam. This phenomenon becomes a social construction of suwuk and azimat which are considered to have many benefits from various times. The aim of this research literature to decrypt how to link the religion of Islam against suwuk and fetish practices and highlight the social construction suwuk and azimat in the view of modern society. The results of this study are suwuk and azimat are related to Islam because they use prayers that come from the verses of the Al-Qur’an. This is what makes suwuk and azimat still trusted and practiced in society, besides that the existence of scientific evidence about suwuk by researchers also makes suwuk easily accepted in modern society.